The way we speak [videorecording (DVD)] - Ebright, Ian; Fabian, Patrick; Coconubo, Diana; Rhodes, Kailey (Gravitas Ventures, 2024)
An up-and-coming writer refuses to leave the spotlight when his best friend and debate opponent suffers cardiac arrest, leading to an obsession over his new opponent and a growing rift with his ailing wife.